GAMBARAN PENGELOLAAN TAMAN PENITIPAN ANAK (TPA) SE-KECAMATAN TAMPAN KOTA MADYA PEKANBARU - Nurul Mufida; Wusono Indarto; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is to know how the description of TPA management a district in Tampan Pekanbaru City, subject of research in this research is 42 principals of TPA Tampan district of Pekanbaru City with 8 indicators. The method used is descriptive quantitative method to know the description of management of TPA. Data collection technique is using questionnaire. Based on the results of data analysis obtained the percentage of 8 indicators are: The physical indicators of TPA in Tampan district of Pekanbaru City is (69,64%) then TPA in Tampan district of Pekanbaru City has been categorized as good (G). Indicator of toys and equipment of TPA in Tampan district of Pekanbaru City is (57,54%) so that the TPA of Tampan district of Pekanbaru City has been categorized as good (G). The indicator ratio of baby sitters of TPA in Tampan district of Pekanbaru City is (55,06%) then the TPA of Tampan district of Pekanbaru City has been categorized as less (L). Indicators of daily activities of TPA in Tampan district of Pekanbaru City is (63,09%) then the TPA in Tampan district of Pekanbaru City has been categorized as good (G). The indicator of qualification of baby sitters in TPA in Tampan district of Pekanbaru City is (64,88%) then the TPA in Tampan district has been categorized as good (G). Indicator of adult’s interaction of TPA in Tampan district of Pekanbaru City is (83,63%) then TPA in Tampan district of Pekanbaru City has been categorized as excellent (E). Indicator of the relationship with the parents of TPA in Tampan district of Pekanbaru City is (64,88%) then the TPA in Tampan district of Pekanbaru City has been categorized as good (G). Indicator of licensing and accreditation of TPA in Tampan district of Pekanbaru City is (61,90%) then TPA in Tampan district of Pekanbaru City has been categorized as good (G).Keyword: Child Care Center Management (TPA)